ORGs and mitotic somal translocation — a role in development and disease. (February 2017) - Ostrem, Bridget; Di Lullo, Elizabeth; Kriegstein, Arnold
Highlights: Description of the neural stem and progenitor cells of the developing human neocortex, specifically the origins and current knowledge regarding outer radial glia. Mechanisms involved in mitotic somal translocation and how they may affect development and disease. Disease modeling of outer radial glia and mitotic behavior. Abstract : The evolution of the human brain has been characterized by an increase in the size of the neocortex. Underlying this expansion is a significant increase in the number of neurons produced by neural stem cells during early stages of cortical development. Here we highlight recent advances in our understating of these cell populations, consisting of ventricular radial glia and outer radial glia. We highlight how gene expression studies have identified molecular signatures for radial glial cell populations and outline what has been learned about the mechanisms underlying the characteristic mode of division observed in outer radial glia cells, mitotic somal translocation. Understanding the significance of this behavior may help us explain human cortical expansion and further elucidate neurodevelopmental diseases.